Catering management - Scanlon, Nancy Loman (New Jersey : John Wiley & Son, Inc., 2013)
An essential, up-to-date guide for catering students and professionals, Catering Management, Fourth Edition, covers all aspects of the business, (operations, sales and marketing to food and beverage service, menu planning and design, pricing, equipment, staff training, and more). The new edition is completely revised with information on sustainable and green catering practices, digital menu and proposal design, new catering industry software, and the expansion of the event market. State-of-the art marketing strategies, including social networking, web promotion, and on-demand proposal development, are also covered.
Chapter 1. Historical banqueting -- Chapter 2. Styles of catering operations -- Chapter 3. Catering business development -- Chapter 4. Catering sales and marketing and digital support -- Chapter 5. Catering-menu program -- Chapter 6. Food-and-beverage operational controls -- Chapter 7. Catering-menu pricing and controls -- Chapter 8. Catering-menu design -- Chapter 9. Catering beverage management -- Chapter 10. Quality-service and standards training -- Chapter 11. Managing catering equipment
Includes bibliographical references and index.
Keywords: CATERERS AND CATERING -- MANAGEMENT